Silicon-carbon composite material and preparation method thereof

By depositing liquid silane in large porous porous carbon and carbonizing it, combined with amorphous carbon coating, silicon-carbon composite materials with high specific surface area and low expansion were prepared, which solved the problem of insufficient conductivity and safety of existing porous carbon materials, and achieved the preparation of silicon-carbon composite materials with simple process and low cost.

CN119612491APending Publication Date: 2025-03-14广东宏璟新能源科技有限公司

Patent Information

Application Number
CN202411789827.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing porous carbon materials have shortcomings in terms of electronic conductivity and safety, and the liquid silane has a high decomposition temperature and good air stability, but the process of deposition in porous carbon is complicated and the cost is high.

Method used

Liquid silane is deposited in large porous porous carbon, carbonized, and amorphous carbon is coated on its surface to prepare a silicon-carbon composite material. The method includes mixing a carbon source, a pore-forming agent and a cross-linking agent, preparing porous carbon by heating and passing through a peroxide gas, then mixing the porous carbon with liquid silane and surfactant, reacting at high pressure and carbonizing, and finally depositing in an inert gas to obtain a silicon-carbon composite material.

Benefits of technology

The silicon-carbon composite material prepared by this method has the advantages of reducing expansion, reducing costs, improving specific surface area and cycling performance. The process of using liquid silane is simple, with low cost and good deposition uniformity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612491A_ABST
    Figure CN119612491A_ABST
Patent Text Reader

Abstract

The preparation method of the silicon-carbon composite material comprises the following steps: uniformly mixing a carbon source, a pore forming agent and a cross-linking agent, and introducing peroxide gas into a tubular furnace for sintering to obtain porous carbon; uniformly mixing the porous carbon with liquid silane and a surfactant, and transferring the mixture into a high-pressure reaction kettle for reaction to obtain a silicon-carbon precursor; and introducing the obtained material into a carbon source gas containing a heteroatom gas for deposition to obtain the silicon-carbon composite material. The obtained material generates porous carbon with high strength and high pore volume by utilizing the cross-linking agent and the pore-forming agent thereof, so that the expansion is reduced; and the liquid silane has the characteristics of low decomposition temperature, low cost and high safety performance, so that the specific capacity is improved, and the cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material preparation, in particular to a silicon-carbon composite material and a preparation method thereof. Background Art

[0002] The new silicon-carbon material is composed of porous carbon and nano-silicon deposited in the pores. The current porous carbon is mainly prepared by biomass or resin activation, and has problems such as poor electronic conductivity. At the same time, the use of silane gas and air is prone to explosion, which poses a great safety hazard. Liquid silane has the advantages of high decomposition temperature, good stability with air and low cost. When deposited in porous carbon, it has the advantages of simple preparation process, low cost and good deposition uniformity. Summary of the invention

[0003] In order to reduce the expansion of silicon-carbon materials and reduce their costs, the present invention prepares a silicon-carbon composite material by depositing liquid silane in large-pore porous carbon, carbonizing it, and coating amorphous carbon on its surface. At the same time, a preparation method of the silicon-carbon composite material is provided.

[0004] A method for preparing a silicon-carbon composite material, characterized in that it comprises the following steps:

[0005] Step S1:

[0006] The carbon source, pore former and cross-linking agent are uniformly mixed according to the mass ratio of carbon source: pore former: cross-linking agent = 100: 5-20: 1-5, and heated to 500-800° C. in a tube furnace, and peroxide gas is introduced at a flow rate of 100-500 SCCM for 60-600 minutes to obtain porous carbon;

[0007] Step S2:

[0008] According to the mass ratio of porous carbon: liquid silane: surfactant = 100: 80-120: 1-5, the porous carbon, liquid silane and surfactant are evenly mixed, and transferred to a high-pressure reactor at a temperature of 50-120° C. and a pressure of 1.5-3.5 MPa for reaction for 1-6 hours, filtered, and vacuum dried to obtain a silicon-carbon precursor;

[0009] Step S3:

[0010] The silicon-carbon precursor is transferred to a tubular furnace, and an inert gas is introduced to exhaust the air in the tube, and the furnace is heated to 500-700°C. A carbon source gas containing heteroatom gas (volume ratio, carbon source gas: heteroatom gas = 10:1-5) is introduced at a flow rate of 100-500 SCCM for deposition for 30-300 minutes. The furnace is then cooled to room temperature in an inert gas to obtain a silicon-carbon composite material.

[0011] In step S1, the carbon source is one of coal tar, petroleum asphalt, amino resin, and furfural resin; the pore-forming agent is one of polyethylene, polymethyl methacrylate, and polyurethane; the cross-linking agent is one of benzaldehyde, trioxymethylene, and formaldehyde; and the peroxide is one of hydrogen peroxide, acetic acid peroxide, di-tert-butyl peroxide, peroxidase, and lauroyl peroxide.

[0012] In step S2, the liquid silane is one of propyltrichlorosilane, dimethylchlorosilane, triisopropylchlorosilane, and phenyldichlorosilane.

[0013] In step S2, the surfactant is one of stearic acid, oleic acid and lauric acid.

[0014] The heteroatom compound in step S3 is one of ammonia, phosphine, hydrogen sulfide and boron.

[0015] Beneficial effects:

[0016] 1. Mix the carbon source, pore former and cross-linking agent, use the macroporous structure left by the pore former during the carbonization process to increase the pore volume of the porous carbon, and use the chemical groups on the surface of the cross-linking agent to form -COC- chemical bonds with carbon to form a nanopore structure, which is conducive to accommodating more nano-silicon to increase the specific capacity.

[0017] 2. Liquid silane has the advantages of low cost, high safety performance and uniform deposition compared to gaseous silicon carbon. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is the SEM image of the silicon-carbon composite material prepared in Example 1. DETAILED DESCRIPTION

[0019] Example 1

[0020] A method for preparing a silicon-carbon composite material comprises the following steps:

[0021] Step S1:

[0022] 100 g of coal tar, 10 g of polyethylene and 3 g of benzaldehyde were mixed evenly, and heated to 650° C. in a tube furnace, and hydrogen peroxide gas was introduced at a flow rate of 300 SCCM for 300 min to obtain porous carbon;

[0023] Step S2:

[0024] 100 g of porous carbon was mixed with 100 g of propyltrichlorosilane and 3 g of stearic acid, and the mixture was transferred to a high-pressure reactor and reacted for 3 h at a temperature of 80 ° C and a pressure of 2.5 MPa, filtered, and vacuum dried at 80 ° C for 24 h to obtain a silicon-carbon precursor;

[0025] Step S3:

[0026] The silicon-carbon precursor was transferred to a tubular furnace, and argon inert gas was introduced to exhaust the air in the tube, and the tube was heated to 600°C. Ethylene gas containing ammonia gas (volume ratio, ethylene gas: ammonia gas = 10:3) was introduced at a flow rate of 300 SCCM for deposition for 150 minutes. The tube was then cooled to room temperature in argon inert gas to obtain a silicon-carbon composite material.

[0027] Example 2

[0028] A method for preparing a silicon-carbon composite material comprises the following steps:

[0029] Step S1:

[0030] 100 g of petroleum asphalt, 5 g of polymethyl methacrylate and 1 g of trioxymethylene were mixed evenly, and heated to 500° C. in a tube furnace, and peracetic acid gas was introduced at a flow rate of 500 SCCM for 600 min to obtain porous carbon;

[0031] Step S2:

[0032] 100 g of porous carbon was mixed evenly with 80 g of dimethylchlorosilane and 1 g of oleic acid, and the mixture was transferred to a high-pressure reactor for reaction at a temperature of 50° C. and a pressure of 3.5 MPa for 6 h, filtered, and vacuum dried at 80° C. for 24 h to obtain a silicon-carbon precursor;

[0033] Step S3:

[0034] The silicon-carbon precursor was transferred to a tubular furnace, and argon inert gas was introduced to exhaust the air in the tube, and the tube was heated to 500°C. Acetylene gas containing phosphine gas (volume ratio, acetylene gas: phosphine gas = 10:1) was introduced at a flow rate of 100 SCCM for deposition for 300 minutes. The tube was then cooled to room temperature in argon inert gas to obtain a silicon-carbon composite material.

[0035] Embodiment 3:

[0036] A method for preparing a silicon-carbon composite material comprises the following steps:

[0037] Step S1:

[0038] 100 g of amino resin, 20 g of polymethyl methacrylate and 5 g of trioxymethylene were mixed evenly, and heated to 800° C. in a tube furnace, and peroxidase gas was introduced at a flow rate of 100 SCCM for 60 min to obtain porous carbon;

[0039] Step S2:

[0040] 100 g of porous carbon was mixed evenly with 120 g of triisopropylsilyl chloride and 5 g of lauric acid, and the mixture was transferred to a high-pressure reactor for reaction at a temperature of 120° C. and a pressure of 1.5 MPa for 1 h, filtered, and vacuum dried at 80° C. for 24 h to obtain a silicon-carbon precursor;

[0041] Step S3:

[0042] The silicon-carbon precursor was transferred to a tubular furnace, and argon inert gas was introduced to exhaust the air in the tube, and the tube was heated to 700°C. Methane gas containing hydrogen sulfide gas (volume ratio, methane gas: hydrogen sulfide gas = 10:5) was introduced at a flow rate of 500 SCCM for deposition for 30 minutes. The tube was then cooled to room temperature in argon inert gas to obtain a silicon-carbon composite material.

[0043] Comparative Example 1:

[0044] The difference from Example 1 is that polyethylene and benzaldehyde are not added in step S1, and the rest is the same as Example 1.

[0045] Comparative Example 2:

[0046] The difference from Example 1 is that gaseous silane (disilane) is used to replace liquid silane polyethylene, and the rest is the same as Example 1. The preparation method is as follows: 100g of the porous carbon in step S1 of Example 1 is transferred to a fluidized bed, heated to 500°C, and introduced a disilane mixed gas (volume ratio, disilane: nitrogen = 1:10) at a flow rate of 100ml / min for 60min; then the introduction of the disilane mixed gas is stopped, heated to 600°C, and ethylene gas containing ammonia gas (volume ratio, ethylene gas: ammonia gas = 10:3) is introduced at a flow rate of 300SCCM for deposition for 150min, and then the temperature is lowered to room temperature under argon inert gas to obtain a silicon-carbon composite material.

[0047] Test Example 1: Physical and chemical and button cell tests

[0048] According to the method in the national standard GB / T38823-2020 "Silicon Carbon", the tap density, specific surface area, and specific capacity of the silicon-carbon composite materials obtained in Examples 1-3 and Comparative Examples 1-2 were tested respectively; the powder resistivity was tested using a four-probe test material before testing; the test results are shown in Table 1 below.

[0049] Button cell battery test:

[0050] The silicon-carbon composite materials obtained in Examples 1-3 and Comparative Examples 1-2 were used as active materials for negative electrode plates of batteries and were respectively prepared and assembled into 9 button batteries, which were marked as A1, A2, A3, B1, and B2 in sequence;

[0051] The specific preparation process of each button battery is as follows: Preparation of battery negative electrode sheet: Adding binder, conductive agent and solvent to each silicon-carbon composite material (as the active material of battery negative electrode sheet) corresponding to Examples 1-3 and Comparative Examples 1-2, stirring and slurrying, coating on copper foil, drying and rolling to obtain each battery negative electrode sheet; wherein, the binder is LA132 binder, the conductive agent is SP (conductive carbon black), and the solvent is double distilled water, and the ratio is: silicon-carbon composite material: SP: LA132: double distilled water = 95g: 1g: 4g: 220mL; Preparation of button battery: The electrolyte is Li PF 6 Solution, in which LiPF 6 The concentration is 1.1 mol / L, and the solvent is a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DMC) in a weight ratio of 1:1; a metal lithium sheet is used as the counter electrode, and polyethylene (PE) is used as the diaphragm. The simulated battery is assembled in an argon-filled glove box, and the electrochemical performance is carried out on a Wuhan Blue Electric CT2001A battery tester. The test conditions are: the charge and discharge voltage range is 0.005V to 2.0V, and the charge and discharge rate is 0.1C; at the same time, the rate performance (0.1C / 1C) and cycle performance (test conditions are: 0.1C / 0.1C, 100 cycles) of the button battery are tested, and the full-charge expansion of the negative electrode sheet of the button battery is tested; the test results are shown in Table 1 below.

[0052] Table 1

[0053]

[0054] It can be seen from Table 1 above that the silicon-carbon composite materials provided in Examples 1-3 of the present application have a high specific surface area and a low DCR, a high first discharge specific capacity, and a first efficiency; the reason is that the material is doped with a pore-forming agent to increase the specific surface area of ​​the material and increase the pores, reduce expansion, and improve the cycle performance; at the same time, the liquid silane used in the example material has high silicon crystallinity and low impedance, which improves the rate performance of the material.

[0055] Test Example 2: Soft-pack battery test

[0056] The silicon-carbon composite materials obtained in Examples 1-3 and Comparative Examples 1-2 were doped with 90% artificial graphite as negative electrode materials (i.e., negative electrode plates), and the ternary material LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 The positive electrode material, electrolyte and separator are assembled into a 5Ah soft-pack battery; the separator of the soft-pack battery is Celegard 2400, and the electrolyte is LiPF 6 Solution, in which LiPF 6The solvent of the solution is a mixed solution of EC and DEC with a volume ratio of 1:1, LiPF 6 The concentration is 1.3 mol / L; the soft-pack batteries made of the corresponding silicon-carbon composite materials in Examples 1-3 and Comparative Examples 1-2 are marked as C1, C2, C3, D1, D2 and their corresponding negative electrode sheets, and the liquid absorption capacity and sheet resistivity of each negative electrode sheet are tested. The test results are shown in Table 2 below;

[0057] The test process of liquid absorption capacity is as follows: use a 1mL burette and absorb electrolyte VmL, drip electrolyte on the surface of the negative electrode, and count until the electrolyte is completely absorbed, and record the time t; and test the resistivity of the electrode through a membrane resistance tester

[0058] Table 2

[0059] Silicon-carbon composite materials used Liquid suction speed (S) Electrode sheet resistivity (Ω·cm) Example 1 65 0.77 Example 2 77 0.63 Example 3 58 0.89 Comparative Example 1 98 1.12 Comparative Example 2 83 1.68

[0060] It can be seen from Table 2 above that the liquid absorption capacity and the electrode resistivity of the negative electrode plates made by the silicon-carbon composite materials provided in Examples 1-3 of the present application are significantly better than those in Comparative Examples 1-2. The main reason may be that: the specific surface area of ​​the silicon-carbon composite materials provided in this embodiment improves the liquid absorption capacity of the material and its low powder resistivity, thereby reducing the resistivity of its electrode plates.

[0061] Test Example 3: Rate performance test of soft pack battery

[0062] The conditions for the rate performance test are:

[0063] The charge and discharge voltage range is 2.5-4.2V, the temperature is 25±3.0℃, and each button cell is charged at 1.0C, 3.0C, and 5.0C, and discharged at 1.0C;

[0064] Table 3

[0065]

[0066] According to Table 3 and Figure 1 It can be seen that the rate charging performance of the soft-pack battery made using the silicon-carbon composite material provided by Examples 1-3 of the present application is significantly better than that of Comparative Examples 1-3, that is, the soft-pack battery made by the examples of the present application has a shorter and faster charging time. The reason may be that: the examples of the present application have low powder conductivity and high specific surface area to improve the rate performance of the material.

[0067] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a silicon-carbon composite material, characterized in that: The steps include: Step S1: The carbon source, pore former and cross-linking agent are uniformly mixed according to the mass ratio of carbon source: pore former: cross-linking agent = 100: 5-20: 1-5, and heated to 500-800° C. in a tube furnace, and peroxide gas is introduced at a flow rate of 100-500 SCCM for 60-600 minutes to obtain porous carbon; Step S2: According to the mass ratio of porous carbon: liquid silane: surfactant = 100: 80-120: 1-5, the porous carbon, liquid silane and surfactant are evenly mixed, and transferred to a high-pressure reactor at a temperature of 50-120° C. and a pressure of 1.5-3.5 MPa for reaction for 1-6 hours, filtered, and vacuum dried to obtain a silicon-carbon precursor; Step S3: The silicon-carbon precursor is transferred to a tubular furnace, and an inert gas is introduced to exhaust the air in the tube, and the furnace is heated to 500-700°C. A carbon source gas containing heteroatom gas (volume ratio, carbon source gas: heteroatom gas = 10:1-5) is introduced at a flow rate of 100-500 SCCM for deposition for 30-300 minutes. The furnace is then cooled to room temperature in an inert gas to obtain a silicon-carbon composite material.

2. The method for preparing a silicon-carbon composite material according to claim 1, characterized in that: In step S1, the carbon source is one of coal tar, petroleum asphalt, amino resin, and furfural resin; the pore-forming agent is one of polyethylene, polymethyl methacrylate, and polyurethane; the cross-linking agent is one of benzaldehyde, trioxymethylene, and formaldehyde; and the peroxide is one of hydrogen peroxide, acetic acid peroxide, di-tert-butyl peroxide, peroxidase, and lauroyl peroxide.

3. The method for preparing a silicon-carbon composite material according to claim 1, characterized in that: In step S2, the liquid silane is one of propyltrichlorosilane, dimethylchlorosilane, triisopropylchlorosilane, and phenyldichlorosilane.

4. The method for preparing a silicon-carbon composite material according to claim 1, characterized in that: In step S2, the surfactant is one of stearic acid, oleic acid and lauric acid.

5. The method for preparing a silicon-carbon composite material according to claim 1, characterized in that: The heteroatom compound in step S3 is one of ammonia, phosphine, hydrogen sulfide and boron.

Citation Information

Patent Citations

  • Silicon carbon composite material, preparation method thereof as well as lithium ion battery

    CN103236525A

  • Porous hard carbon negative electrode material based on asphalt as well as preparation method and application of porous hard carbon negative electrode material

    CN115676804A

  • Silicon-carbon composite material as well as preparation method and application thereof

    CN116014100A

  • Low-expansion silicon-carbon composite material and preparation method thereof

    CN117486194A

  • Preparation method of multi-element doped silicon-carbon composite material

    CN118231626A

Cited By

  • Silicon-carbon negative electrode material and preparation method and application thereof

    CN120184227A

  • A silicon-carbon negative electrode material and its preparation method and application

    CN120184227B

  • Silicon-carbon negative electrode material and fluidization preparation method thereof

    CN121484037A

  • Silicon-carbon composite material, preparation method thereof, electrode and battery

    CN121687934A

  • Silicon-carbon composite material, method for preparing the same, electrode, and battery

    CN121687934B